Kompetensi Manajerial Kepala Sekolah, Kompensasi dan Kepuasan Kerja Terhadap Kinerja Guru Pada SMK Swasta Di Kota Batam - Suhardi (Coopetition : Jurnal Ilmiah Manajemen, 2018)
In Teaching and Learning Process, teachers have a very decisive position of successful learning, in the hands of successful or not achievement of teaching and learning goals in school. And as the driving force, the principal who is given the task to lead the school should also be able to develop and improve the performance of subordinates ie teachers. The result of this research is partial of headmaster's managerial competence, job satisfaction have positive and significant influence to teacher performance, while compensation has negative and insignificant effect on teacher performance in SMK Swasta in Batam City Riau Islands Province but simultaneously managerial competence, compensation and satisfaction work has a positive and significant impact on the performance of teachers in private SMK in Batam City Riau Islands Province.